2012
DOI: 10.1073/pnas.1202977109
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II distribution in dendritic cells and B cells is determined by ubiquitin chain length

Abstract: Dendritic cells (DCs) and B cells present antigen-derived peptides bound to MHC class II (MHC II) molecules for recognition by CD4-positive T lymphocytes. DCs control the intracellular traffic of peptide-MHC II complexes by regulating the ubiquitination of MHC II. In resting or "immature" DCs, ubiquitinated MHC II molecules are targeted to lysosomes, but upon pathogen-induced "maturation," ubiquitination is down-regulated and MHC II can accumulate on the plasma membrane of mature DCs. Although B cells constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…When normalized for total expression of MHC-II in each cell type, pMHC-II in freshly isolated spleen B cells and DCs was ubiquitinated to a much greater extent than pMHC-II in BMDCs. As was observed previously (19), pMHC-II isolated from spleen B cells has a short ubiquitin chain length (generally one and two ubiquitin moieties per molecule), whereas ubiquitin chain length of pMHC-II in BMDCs was longer (usually four and five ubiquitin moieties per molecule). We did not observe dramatic differences in ubiquitin chain length in pMHC-II isolated from spleen B cells and spleen DCs.…”
mentioning
confidence: 57%
“…When normalized for total expression of MHC-II in each cell type, pMHC-II in freshly isolated spleen B cells and DCs was ubiquitinated to a much greater extent than pMHC-II in BMDCs. As was observed previously (19), pMHC-II isolated from spleen B cells has a short ubiquitin chain length (generally one and two ubiquitin moieties per molecule), whereas ubiquitin chain length of pMHC-II in BMDCs was longer (usually four and five ubiquitin moieties per molecule). We did not observe dramatic differences in ubiquitin chain length in pMHC-II isolated from spleen B cells and spleen DCs.…”
mentioning
confidence: 57%
“…Although MARCH1 seems to play a more prominent role in controlling pMHCII traffic in DCs , it cannot be excluded that the two ligases act at distinct sites, for example, at the plasma membrane and at the endosomal membrane, leaving dissimilar sorting signatures. In this regard, it was recently shown that sorting of MHCII is highly dependent on the length of the conjugated ubiquitin chain (Ma et al 2012). Specificities of MARCH ligases may differ for distinct MHCII isotypes (Jahnke et al 2012).…”
Section: Sorting Of Mhcii At Mvbsmentioning
confidence: 99%
“…3 In parallel, CD4 C T-cell activation is important for the induction of specific CD8 C T-cell and humoral responses. 4,5 To be presented to B-cells 6 and CD4…”
Section: Antigen Processing and Presentation For T And B-cell Epitopesmentioning
confidence: 99%